Reaction of Exotic Soybean Germplasm to Phakopsora pachyrhizi in Uganda - Oloka, H. K.; Tukamuhabwa, P.; Sengooba, T.; Shanmugasundram, S. (Plant Disease, 2008)
Host plant resistance is the best long-term strategy for managing soybean rust (Phakopsora pachyrhizi) in endemic areas. Resistance breeding efforts are hampered by the presence of several races of the pathogen that often overcome single resistance genes deployed against them. In Uganda, only two soybean cultivars show moderate resistance to Phakopsora pachyrhizi, but this is likely to break down given the aggressive nature of the pathogen. A total of 25 rust tolerant or resistant accessions were imported from the Asian Vegetable Research and Development Centre and screened at Namulonge, in central Uganda. Only 10 accessions, G 33, G 8527, G8586, G 8587, GC 60020-8-7-7-18, GC 87016-11-B-2, GC 87021-26-B-1, SRE-D-14A, SRE-D-14B, and SS 86045-23-2, showed no rust symptoms at growth stage R6 during the three seasons of testing. Soybean rust resistance genes Rpp1, Rpp3, and Rpp4 did not confer resistance at Namulonge; gene Rpp2 was effective.
Keywords: Exotic Soybean Germplasm; Phakopsora pachyrhizi; Uganda